An evaluation of computed brain scans in children at Chris Hani Baragwanath Hospital - Vallabh, Preeteeben (My University, 2011)
Background: Computed tomography (CT) was introduced 40 years ago and it remains an essential part of medical practice. The indications for CT brain scans vary in different centres depending on the availability of scanners and financial resources. There is no data on the indications and results of CT brain scans in children at Chris Hani Baragwanath (CHB) Hospital. Aims: The indications for CT brain scans were quantitated and the overall results of the scans were assessed. The rate of radiological abnormalities by referral diagnosis was evaluated. Methodology: 361 Children undergoing CT brain scans were identified in a four month period from 22/01/2004 to 21/05/2004, and their records were prospectively reviewed. Results: The ages ranged from 2 days to 14 years. There were 213 males and 148 females with a male: female ratio of 1.4:1. Seizures was the commonest indication for scans (25.8%) in this study. The six common indications (partial and generalized seizures, trauma, central nervous system [CNS] infections, macrocephaly and psychomotor retardation) accounted for 67.6% of the scans. There were 233 (63.5%) abnormal scans. Cerebral atrophy was the commonest finding, present in 58 (16.1%) scans. Discussion: A high rate of positive scans was detected in this study, with intracranial infections featuring prominently (9.7%). This high yield of positive scans in the study population suggests the need for more scanner facilities at CHB hospital. DPDoFcuments Complete Click Here & Upgrade Expanded Features Unlimited Pages
MSc (Med), Child Health Neurodevelopment, University of the Witwatersrand, Faculty of Health Sciences
Keywords: brain scans; children